Corporate social responsibility strategy and economic business value of multinational companies in emerging economies: The mediating role of corporate reputation. Issue 1 (18th June 2019) - Abugre, James B.; Anlesinya, Alex
Abstract: Corporate social responsibility (CSR) and business value of multinational corporations are significantly tied to corporate reputation. In this work, we investigated the mediating influence of corporate reputation of multinational companies (MNCs) on their CSR strategy and economic business value. The study adapted a quantitative methodology with a sample of respondents from multinational corporations in Ghana—an emerging economy. Drawing from 267 employees of MNCs in Ghana, a structural equation modelling and bootstrapping analysis are used to assess the hypothesised relationship. The results showed that CSR strategy positively and significantly predicts economic business value and corporate reputation of MNCs. Findings also showed that corporate reputation mediates the relationship between CSR strategy and economic business value of MNCs operating in emerging economies. This study suggests that good corporate reputation significantly influences MNCs' strategy in corporate responsibility and economic business value. Thus, management of MNCs can enhance their corporate business objectives through sustainability practices.